Prospective multicentre study on barbed reposition pharyngoplasty standing alone or as a part of multilevel surgery for sleep apnoea. (6th November 2017) - Montevecchi, F.; Meccariello, G.; Firinu, E.; Rashwan, M. S.; Arigliani, M.; De Benedetto, M.; Palumbo, A.; Bahgat, Y.; Bahgat, A.; Lugo Saldana, R.; Marzetti, A.; Pignataro, L.; et al.
Abstract : Objectives: The aim of this study was to demonstrate in a prospective multicentre study that Barbed Reposition Pharyngoplasty (BRP) procedure is safe and effective in management of obstructive sleep apnoea/hypopnea syndrome (OSAHS) patients. Design: Prospective study. Setting: Multicentre study. Participants: Patients suffering from obstructive sleep apnoea. Main outcomes measures: Values of postoperative apnoea‐hypopnea index (AHI), oxygen desaturation index (ODI), epworth sleepiness scale (ESS). Results: 111 Barbed Reposition Pharyngoplasty procedures standing alone or as a part of multilevel surgery for OSAHS, performed between January and September 2016, were analysed in 15 different centres. The average hospitalisation period was 2.5 ± 0.5 days. The mean patient age was 46.3 ± 10.5 years. The average body mass index at the time of the procedure was 27.9 ± 3.2, and the majority of the patients were men (83%). The mean preoperative and postoperative apnoea/hypopnea index was 33.4 ± 19.5 and 13.5 ± 10.3, respectively ( P < .001). The mean preoperative and postoperative ESS score was 10.2 ± 4.5 and 6.1 ± 3.6, respectively ( P < .001). The mean preoperative and postoperative ODI were 29.6 ± 20.7 and 12.7 ± 10.8, respectively ( P < .001). Conclusions: Patients undergoing BRP standing alone or as part of a multilevel approach for the treatment of OSAHS have a reasonable expectation for success with minimal morbidity.